2018
DOI: 10.1038/s41598-018-20958-1
|View full text |Cite
|
Sign up to set email alerts
|

Pyroptosis induced by enterovirus 71 and coxsackievirus B3 infection affects viral replication and host response

Abstract: Enterovirus 71 (EV71) is the primary causative pathogen of hand, foot, and mouth disease (HFMD), affecting children with severe neurological complications. Pyroptosis is a programmed cell death characterized by cell lysis and inflammatory response. Although proinflammatory response has been implicated to play important roles in EV71-caused diseases, the involvement of pyroptosis in the pathogenesis of EV71 is poorly defined. We show that EV71 infection induced caspase-1 activation. Responding to the activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 67 publications
3
36
0
Order By: Relevance
“…As shown in Figure 4A, dramatically increased level of caspase-1 p20, one of the active fragments of caspase-1, was seen in the cells at 12 h of post-infection. As we have demonstrated previously 39 , procaspase-1 and NLRP3, the critical constituents of NLRP3 inflammasome, were also increased due to CVB3 infection ( Figure 4A). These data show that CVB3 infection not only induces the activation of caspase-1, but also increases the level of procaspase-1.…”
Section: Nac Directly Inhibits the Activation Of Caspase-1supporting
confidence: 81%
See 3 more Smart Citations
“…As shown in Figure 4A, dramatically increased level of caspase-1 p20, one of the active fragments of caspase-1, was seen in the cells at 12 h of post-infection. As we have demonstrated previously 39 , procaspase-1 and NLRP3, the critical constituents of NLRP3 inflammasome, were also increased due to CVB3 infection ( Figure 4A). These data show that CVB3 infection not only induces the activation of caspase-1, but also increases the level of procaspase-1.…”
Section: Nac Directly Inhibits the Activation Of Caspase-1supporting
confidence: 81%
“…We previously demonstrated that CVB infection induced caspase-1 activation. surprisingly, we found that inhibition of caspase-1 with specific inhibitors not only alleviated the myocardial inflammation but also significantly inhibited viral replication, suggesting a novel therapeutic strategy against CVB-induced myocarditis 39 . N-acetyl cysteine (NAC), an amino acid derivative, is among the list of essential medicines issued by the World Health Organization 40 .…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Pyroptosis is characterized by cell lysis and an inflammatory response and may occur as an antiviral immune response to virus infection. For instance, enterovirus 71 (EV71) and coxsackievirus B3 (CVB3) infections activate host pyroptosis, which is accompanied by IL-1β and IL-18 secretion [64]. Necroptosis is marked by rupture of the plasma membrane and release of proinflammatory damage-associated molecular patterns (DAMPs), and plays pro-inflammatory roles against virus infection [65].…”
Section: Apoptosismentioning
confidence: 99%